Human Single-chain Variable Fragments Neutralize Pseudomonas aeruginosa Quorum Sensing Molecule, 3O-C12-HSL, and Prevent Cells From the HSL-mediated Apoptosis - Santajit, Sirijan; Seesuay, Watee; Mahasongkram, Kodchakorn; Sookrung, Nitat; Pumirat, Pornpan; Ampawong, Sumate; Reamtong, Onrapak; Chongsa-Nguan, Manas; Chaicumpa, Wanpen; Indrawattana, Nitaya (Frontiers in Microbiology, 2020)
The quorum sensing (QS) signaling molecule, N-(3-oxododecanoyl)-L-homoserine lactone (3O-C12-HSL), contributes to the pathogenesis of Pseudomonas aeruginosa by regulating expression of the bacterial virulence factors that cause intense inflammation and toxicity in the infecting host. As such, the QS molecule is an attractive therapeutic target for direct-acting inhibitors. Several substances, both synthetic and naturally-derived products, have shown effectiveness against detrimental 3O-C12-HSL activity. Unfortunately, these compounds are relatively toxic to mammalian cells, which limits their clinical application. In this study, fully human single-chain variable fragments (HuscFvs) that bound to P. aeruginosa haptenic 3O-C12-HSL were generated based on the principle of antibody polyspecificity and molecular mimicry of antigenic molecules. The HuscFvs neutralized 3O-C12-HSL activity and prevented mammalian cells from the HSL-mediated apoptosis, as observed by Annexin V/PI staining assay, sub-G1 arrest population investigation, transmission electron microscopy for ultrastructural morphology of mitochondria, and confocal microscopy for nuclear condensation and DNA fragmentation. Computerized homology modeling and intermolecular docking predicted that the effective HuscFvs interacted with several regions of the bacterially-derived ligand that possibly conferred neutralizing activity. The effective HuscFvs should be tested further in vitro on P. aeruginosa phenotypes as well as in vivo as a sole or adjunctive therapeutic agent against P. aeruginosa infections, especially in antibiotic-resistant cases.